Behavior of Holstein milking cows exposed to different environmental conditioning systems - Vilela, R.A. (2012)
Objectives: The aim of the study was to evaluate the behavior of dairy cows in summer in relation to the environmental conditioning system (fans with or without misting). Materials and Methods: Twenty Holstein lactating cows were allotted in free-stall pens, divided in two groups: VN ? with fans plus misting; V ? only with fans. The behavior was estimated as time standing and eating, ruminating and idling activities. Data were registered during 4 days by scan method, from 0600h to 1800h, with 30 minutes intervals. Results: Air temperature and relative humidity were registered and indicated a heat stress situation, with maximum temperatures of 32oC and 87% of relative humidity. We observed high values of in standing posture and eating activity on 11h30, 1630h and 1700h hours of VN animals (P <0.05). High frequency for ruminating and idling activities were found at 1700h and 1630h, respectively, for the V animals (P <0.05). Conclusions: The use of fans as the only resource of thermal comfort in these experimental conditions was inefficient when compared to the combination of fans and misting, which give a better thermal comfort condition, allowing cows to feed for long periods, even during the hottest hours of the day, indicating less heat stress.